The current and future social image of the political process in Iraq among university students - Abass, Zalzalah Mahmood (International Journal of Psychosocial Rehabilitation, 2020)
The social image achieves a great role in forming a collective approach around the various subjects, groups and various situations of a social, cultural or political nature, so the current study comes as a scientific attempt to use a political phenomenon from a social point of view, which is the phenomenon of the political process in its current and future image. The researcher assisted two scales with two images of the current and future social image, in which they have the psychometric properties that must be provided to measure any phenomenon. The study found that the research sample carries a negative current and future social image, there is no difference between the gender (males or females) and the Specialty (scientific or human) and there is a positive correlation between the current and future social image of the political process in Iraq.